ARTS DEPARTMENT OF SEMARANG STATE UNIVERSITY’S VIDEO PROFILE DESIGN - Anggitatama, Yogi Putra (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2020)
The Design of the profile video aims to apply the knowledge and skills gained during lectures into the form of works related to Visual Communication Design, especially videography, to create works in the form of video profiles of the Department of Fine Arts, Semarang State University, and to introduce the Department of Fine Arts, Semarang State University to the wider community. There are 2 tools used in designing the video profile, namely hardware and software. Hardware consists of a camera, tripod, drone, stabilizer, lighting, recorder, and laptop. The software used is Adobe Premiere Pro and FL Studio. The design of this profile video goes through several stages of work in the order: preliminary, pre-production, production, and post-production. The concept used is simple, elegant, and informative so that the audience can understand the informative provided and make people interested. The results obtained from designing a profile video are in the form of a lot of positive insights when published, namely through the study project exhibition, uploading on Instagram and Youtube. The study project exhibition received quite a lot of visitors and also received a positive response in the form of a message. On Instagram, it got 1600+ viewers and 410 likes. Meanwhile, the Youtube media gets 100 viewers